2a+6a=4a+3

Simple and best practice solution for 2a+6a=4a+3 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 2a+6a=4a+3 equation:


Simplifying
2a + 6a = 4a + 3

Combine like terms: 2a + 6a = 8a
8a = 4a + 3

Reorder the terms:
8a = 3 + 4a

Solving
8a = 3 + 4a

Solving for variable 'a'.

Move all terms containing a to the left, all other terms to the right.

Add '-4a' to each side of the equation.
8a + -4a = 3 + 4a + -4a

Combine like terms: 8a + -4a = 4a
4a = 3 + 4a + -4a

Combine like terms: 4a + -4a = 0
4a = 3 + 0
4a = 3

Divide each side by '4'.
a = 0.75

Simplifying
a = 0.75

See similar equations:

| x-1=24 | | 3n-2(4n-3)=-2n | | -4(x-2)+2(x-1)=40 | | y(5-y)=176 | | 2a+6=3+4a | | -3x-2y-6=0 | | 3(x-2)-5(2x+10)=3 | | x+x=26 | | 2+6a=3+4a | | x^2y^2-11x^2-y^2+11= | | 3x-6-10x+10=3 | | 4x-9=126 | | 7(x+4)=7x-4 | | 2u+u=15+12 | | 3x+x+2=-4x+2 | | 4y+2+3y+4=9y+6 | | 4x-2y=.16 | | 25x+50(51-x)=1675 | | -x+8=4x-7 | | 7x-17=3(x-4) | | -11-1=4u-u | | 5-2(x-1)=7 | | 2*-3=x | | -2.25v+0.8=0.875 | | x^2+45x+400=0 | | x^2+45x+400=0 | | 2x-6=2x-28 | | 6+60x+150x^2=0 | | 30-6x=-15y | | f(x)=2x^2-3X-11 | | -3x^2-8x-7=0 | | 3x^2(-2x)=8 |

Equations solver categories